2008
DOI: 10.1007/s11663-008-9182-2
|View full text |Cite
|
Sign up to set email alerts
|

Selective Removal of Copper(II) and Nickel(II) from Aqueous Solution Using the Chemically Treated Chitosan: Factorial Design Evaluation

Abstract: In the present work, the adsorption of Cu(II) and Ni(II) ions from their mixture solution by raw and chemically modified chitosan has been studied. The full factorial design methodology was employed to reduce the total number of experiments. Analysis of variance and student's t-test have been performed for Ni(II) and Cu(II) removal efficiency and for the ratio of their removal. The two main factors considered were pH of solution (at two levels 2.8 and 4.8) and contact time (at two levels: 20 minutes and 18 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…It is often used as an adsorbent for protein, dye, metal, lipid etc. [ 20 , 21 , 22 , 23 , 24 , 25 ]. The amino, hydroxyl, and N -acetyl reactive groups on chitosan structure could interact with adsorbates by electrostatic interaction, hydrogen bonding and hydrophobic interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is often used as an adsorbent for protein, dye, metal, lipid etc. [ 20 , 21 , 22 , 23 , 24 , 25 ]. The amino, hydroxyl, and N -acetyl reactive groups on chitosan structure could interact with adsorbates by electrostatic interaction, hydrogen bonding and hydrophobic interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Montilla et al [ 22 ] recovered 90% β-LG with a protein purity of 95% by adjusting the pH of the β-LG-chitosan complex solution to 9. Sepehran et al [ 23 ] reported that raw and formaldehyde modified chitosan can selectively adsorb Cu 2+ and Ni 2+ ions from their mixture solution. The adsorption selectivity of chitosan can be enhanced by chemical treatment and regulating pH and contact time.…”
Section: Introductionmentioning
confidence: 99%
“…Berdasarkan grafik tersebut dimungkinkan bahwa pada waktu 5 jam, kondisi adsorpsi sudah mencapai kesetimbangan dan merupakan waktu kontak minimal dalam aplikasi adsorpsi terhadap ion logam Ni(II) oleh kitosantripolifosfat. Semakin lama waktu kontak antara adsorben dengan adsorbat, maka semakin banyak molekul adsorbat yang teradsorpsi hingga mencapai kondisi maksimum adsorben [14].…”
Section: Variasi Waktu Kontakunclassified
“…[1] Due to its cost, it is incentive to recover it from waste solutions. There are many technologies involving chemical and physical processes which have been developed over the past years to remove hazardous metal ions, such as chemical precipitation, [2,3] adsorption, [4][5][6][7][8][9][10][11][12] ion exchange, [13,14] electrochemical technique, [15][16][17] , and membrane processes, [18][19][20] ; however, all of them have drawbacks. Chemical precipitation requires extremely long settling time and produces a large amount of sludge; ion exchange and adsorption are expensive and require frequent regeneration; and membrane processes suffer from operational problems due to fouling of membranes which can be reduced by several approaches, e.g., by feed pretreatment and treatment of the membrane surface.…”
Section: Introductionmentioning
confidence: 99%